Critical Design Strategy of Thermogalvanic Hydrogels for Low‐Grade Heat Harvesting - Wentao Lin; Shukai Wu; Shuo Niu; Zhe Hu; Guangming Chen; Zhuoxin Liu; Yang Huang; Chao Fang (Advanced Science)
Abstract Low‐grade heat, typically defined as heat at temperatures below 100 °C, is abundant and ubiquitous in the daily environment. However, it is often wasted due to the lack of efficient recovery methods. Thermocells (TECs), which leverage the thermogalvanic effect, provide a promising solution for directly converting low‐grade heat to electricity. Recently, thermogalvanic hydrogels (THs) have emerged as an innovative class of materials for high‐performance TECs due to their giant thermopower, high flexibility, biocompatibility, and low cost. This review comprehensively summarizes the latest advancement in TH research, with a particular focus on the promising design strategies. First, the fundamental mechanisms underlying thermoelectrochemical conversion in THs are systematically scrutinized. Second, the key metrics are outlined for evaluating TECs. Third, current strategies are highlighted for enhancing the thermoelectrochemical performance of THs, including the modifications of polymer matrix, liquid phase, additives, and others. Additionally, the current applications of TH‐based devices are examined in energy harvest and sensing. Finally, the remaining challenges are discussed in the field and provide a forward‐looking perspective on the future development of THs.